Entre livres e oficiais: a expansão do ensino normal em São Paulo (1927-1933) - Inoue, Leila Maria [UNESP] (2015)
This Doctorate thesis has as subject the instruction of teachers in the State of São Paulo and to analyze the expansion process of the Standard Teaching, applied at Standard Schools where teachers were instructed and educated, in the western region of the São Paulo state between 1927 and 1933. This period comprises the year of the implementation of the Public Instruction in the São Paulo state in 1927, organized by Amadeu Mendes the Public Instruction General Director of that time, and finalized in 1933 with the implementation of the Education Code elaborated by Fernando de Azevedo. The sources of this study are documents from the permanent archives of the State School Leonidas do Amaral Vieira, in Santa Cruz do Rio Pardo, and the Nossa Senhora Auxiliadora School in Lins, which were old Free Standard Schools located in the western region of São Paulo. The development of this thesis was based on the prospects of Cultural History extracted from the studies performed by Carvalho, Chartier and Certeau. Chartier (1990, p.16-17), believes that the cultural history, as we understand, has as its main objective to identify how in different places and times a particular social reality is constructed, thought and influenced to read. As a result, considering the low literate rate, the increase in the school-age population - particularly in new areas of settlement - and the shortage of standard teachers - together with the lack of financial resources - that the state government equated the Free Standard Schools to the Official Standard Schools to expand the Standard Education and train teachers to meet the demand, and, therefore expanding primary education. I also believe that the 1927 Reformation was important to extend the Standard School to remote areas of large urban centers. The analysis of the two schools located in the west of São Paulo indicates that the expansion of the Standard School was for students who could afford the studies and...